2021
DOI: 10.1177/17588359211018022
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of predictive factors for single first-generation EGFR-TKI use for more than 5 years in patients with advanced non-small cell lung cancer: Taiwan multicenter TIPS-5 study

Abstract: Background: The relative importance of predictive factors for advanced non-small cell lung cancer (NSCLC) patients on epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) treatment remains unclear. Materials and methods: We retrospectively enrolled advanced NSCLC patients with single first-generation EGFR-TKI treatment for ⩾5 years (Y) in Taiwan. Clinical data was collected and compared with those of another cohort with single first-line EGFR-TKI treatment for <5 Y. Plasma cell-free DNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[34][35][36] Older age, poor performance status, and CNS metastasis are known unfavorable clinical factors associated with survival and outcome in advanced EGFR-mutated patients. 37,38 Among the patients with unknown T790M status in our study, 62 patients still received osimertinib (n = 25) and other 3G EGFR-TKIs (n = 37). Chemotherapy is currently recommended as second-line therapy for EGFRmutated patients without secondary T790M after 1G/2G EGFR-TKI therapy because the genetic alterations in T790M-negative patients are heterogeneous and resistant to osimertinib or other 3G EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 94%
“…[34][35][36] Older age, poor performance status, and CNS metastasis are known unfavorable clinical factors associated with survival and outcome in advanced EGFR-mutated patients. 37,38 Among the patients with unknown T790M status in our study, 62 patients still received osimertinib (n = 25) and other 3G EGFR-TKIs (n = 37). Chemotherapy is currently recommended as second-line therapy for EGFRmutated patients without secondary T790M after 1G/2G EGFR-TKI therapy because the genetic alterations in T790M-negative patients are heterogeneous and resistant to osimertinib or other 3G EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that patients with EGFR-mutated NSCLC with baseline liver and brain metastases had shorter PFS after EGFR-TKI therapy and unfavorable outcomes [ 15 , 24 , 26 28 ]. Our study identified that patients with liver metastasis had shorter PFS than those without liver metastasis, which is consistent with findings in the study by Li et al [ 24 ].…”
Section: Discussionmentioning
confidence: 99%